A Critical View of the De Locomotief Newspaper on Laborers in Java 1864-1870 : Pandangan Kritis Koran De Locomotief Terhadap Buruh di Jawa 1864-1870 - Bambang Rakhmanto; Ilah Nuridah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article examines the representation of labor in the newspaper De Locomotief from 1864 to 1870, when the Dutch East Indies underwent a shift from liberal agrarian policies to a system of forced cultivation. The purpose of this study is to reveal the ideological position of De Locomotief in understanding labor issues in Java and its relationship to colonial political changes at the end of the 19th century. Using the Delpher digital archive of the Koninklijke Bibliotheek as the primary source, historical methods were employed through the stages of heuristics, source criticism, interpretation, and historiography. To analyze the relationship between language, ideology, and power in media texts, Norman Fairclough's Critical Discourse Analysis methodology was used. The research shows that De Locomotief displayed a critical attitude towards colonial policy through its reporting on labor exploitation, contract violations, inadequate wages, and the debunking of the myth of “indigenous laziness” as colonial legitimation. Unlike its contemporary colonial newspapers, such as Java-Bode and Soerabaijasch Handelsblad, De Locomotief always raised labor issues as structural problems. This study confirms that colonial media played an important role in creating critical discussions that contributed to changes in agrarian policy leading up to the enactment of the Agrarische Wet in 1870.